ADAPTATION PROCESS OF NON-SOUTH SULAWESI STUDENTS IN FACING CULTURE SHOCK IN BUSINESS ENGLISH COMMUNICATION STUDY PROGRAM OF UNIVERSITAS NEGERI MAKASSAR - Nur Auliya Sucika Haidir; Riny Jefri; Andi Hajar (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
South Sulawesi is one of the largest islands in Indonesia, has a diverseand rich culture, which provides significant adaptation challenges for students fromother regions. The problem of this research is how the adaptation process of non-South Sulawesi students in dealing with culture shock in the Business EnglishCommunication Study Program at Universitas Negeri Makassar. This researchaims to find out how Business English Communication students adapt tointercultural communication and identify factors that cause culture shock. Thisresearch uses qualitative research method with descriptive design, this researchinvestigates the experiences and challenges faced by these students. Data werecollected through structured interviews with 12 students who came from variousregions outside South Sulawesi. The research identified five stages of culturaladaptation: planning, honeymoon, frustration, adjustment, and resolution. Findingsfrom this study revealed that students experienced both positive and negativeemotions during the adaptation period, which were influenced by differences inlanguage, social norms, and daily life.